Higher Education and the Marriage Market: Educational Attainment, Educational Homogamy, and Inequality - Andres, Lesley (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2022)
The purpose of this article is to examine if educational homogamy patterns are associated intergenerationally, the extent to which today’s couples are homogamous, and how this translates into levels of family income and financial and overall well-being. To examine these relationships, 28 years of longitudinal data from the British Columbia Paths on Life’s Way project are employed. First, changes in marital status, educational completion, and homogamy are examined with the goal of defining these constructs more precisely. Through descriptive statistics, the relationship between educational attainment and related homogamy levels of Paths respondents and their parents is established. Then, the technique of correspondence analysis is used to determine the relationship between assortative mating and the nature and extent of inequality experienced by Paths respondents. Findings reveal that educational homogamy and its intergenerational associations exist and the extent to which it exacerbates inequality in terms of family income levels, contributions to registered investment plans, and physical, mental, and financial well-being in the sample. The findings of this article highlight the value of a post-secondary education in relation to marriage strategies, and the reproduction of inequalities.